Digital in-line holographic imaging of intracellular nanoparticles tagged with TAT peptide - Raghavan, Thiagarajan (2013)
As the field of nanoparticles for biological and medical applications moves on apace, their interaction with cellular membranes remains an enigma. Internalization of nanoparticles in the cell are being studied extensively to acquire knowledge on various physiological properties (i.e. size, charge, permeability and receptor density) governing their interactions with the cell. Analysis and comparisons of various kinds of endocytotic studies are being carried out using several optical techniques. The need to track the temporal efficiency of these molecular movements combined with their positional information at different time frames demands a three-dimensional imaging approach. The resolution of the three-dimensional imaging system should be capable of recording nanoparticle movements whose step size would be in the range of nanometres. In this context, this project is aimed at exploring the capability of Digital In-line holography for imaging the intracellular nanoparticles in fixed cells with a view towards developing this technology for real time temporal investigations in the near future. The experiments involved fluorescence and holographic imaging of two different cell lines with internalized functionalized nanoparticles. A customized digital in-line holography set up was assembled to acquire the holograms of nanoparticle distributions inside the cell. The holograms and fluorescence images were compared to confirm the absence of artifacts due to imaging systems. Then the holograms were reconstructed using an algorithm implemented through MATLAB. The analysis of the images clearly revealed the utility Of in-line holography for acquiring holograms of intracellular nanoparticles and in reconstructing them at different axial distances thereby apparently predicting their axial and spatial distributions. Hence, it is perceived that this project can be further improvised to extract the valuable temporal details at molecular level by applying it in real time imaging. These investigations would lead to a better understanding of transport phenomena across membranes and can be employed in the process of designing and delivering drugs to the targeted domain at the desired instant of time.